1993
DOI: 10.5144/0256-4947.1993.535
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin and Antinuclear Antibodies in Patients with Unexplained Recurrent Abortions

Abstract: In a controlled study on a resident population in Kuwait, 103 patients with unexplained recurrent spontaneous abortions were investigated for the frequency of positive tests for anticardiolipin antibodies (ACA) and antinuclear antibodies (ANA). The frequency of ACA was significantly (P <0.001) higher in patients (32.0%) than in controls (7.1%). Only four patients (3.8%) were positive for both IgG and IgM ACA. The frequency of positive tests for ANA was also significantly (P <0.001) higher in patients (13.6%) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…observed that the ANA-positive rate in women with RPL was 17%, and the miscarriage rate in the next pregnancy was similar to that of women who had RPL and tested negative for ANAs ( 32 ). Additionally, it was reported that the occurrence of subsequent live births was not affected by ANA levels or associated thrombophilia ( 25 ).…”
Section: Presence Of Anas and Its Prognostic Value In Rplmentioning
confidence: 99%
“…observed that the ANA-positive rate in women with RPL was 17%, and the miscarriage rate in the next pregnancy was similar to that of women who had RPL and tested negative for ANAs ( 32 ). Additionally, it was reported that the occurrence of subsequent live births was not affected by ANA levels or associated thrombophilia ( 25 ).…”
Section: Presence Of Anas and Its Prognostic Value In Rplmentioning
confidence: 99%